Scoping Review of Technostress Drivers and Mitigation Strategies in Hybrid Work Environments - I Dewa Gede Sayang Adi Yadnya; Yeni Fajrin; Robby Fauji; Askolani Askolani; Eeng Ahman (JURNAL ECONOMINA, 2026)
Objective: This study aims to systematically analyze the antecedents, impacts, and mitigation strategies of technostress specifically within the context of hybrid work environments. It seeks to address the emerging "digitalization paradox," in which the flexibility of remote work arrangements paradoxically compromises employee psychological well- being and long-term sustainability. Research Design & Methods: A scoping review was conducted in accordance with PRISMA-ScR guidelines to map the evolving landscape of digital stress. The dataset was retrieved from the Scopus database, focusing on peer-reviewed empirical articles published between 2020 and 2025. A final corpus of 50 high- quality studies was analyzed using a dual approach of bibliometric mapping to identify temporal trends and thematic synthesis to consolidate k ey narratives. Findings: The analysis reveals a critical shift in stressors from technical accessibility to "techno-invasion" and the "always-on" culture. Specific phenomena, such as videoconferencing fatigue and cognitive fragmentation, emerged as distinct drivers of exhaustion. The findings highlight a "sustainability gap" in which organizational productivity in hybrid models is often maintained by depleting employees' cognitive resources, leading to accelerated burnout despite reported flexibility. Implications & Recommendations: The study implies that individual coping mechanisms are insufficient to combat systemic technostress. Practical recommendations for management include moving beyond soft wellness programs to implement structural "guardrails," such as formal "Right to Disconnect" policies. Furthermore, leadership training must pivot towards "digital empathy" and asynchronous communication protocols to effectively buffer the physiological strain of virtual work. Contribution & Value Added: This research extends the Job Demands-Resources (JD-R) model by conceptualizing digital tools as "conditional resources" that become demands when boundary management is absent. It contributes a novel conceptual framework that links specific digital antecedents to divergent organizational outcomes, offering a blueprint for designing healthier socio-technical.